2022
DOI: 10.1002/cam4.5549
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Tim‐3 is associated with poor prognosis in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a heterogeneous hematopoietic malignancy originated from leukemia stem cells (LSC). Emerging evidence suggests T-cell immunoglobulin mucin-3(Tim3) as surface marker for LSC. However, the clinical significance and biology of Tim-3 in AML remain to be determined, especially those LSCs. In public AML databases as well as our data, we separated AML patients into Tim-3 high and Tim-3 low subsets using the X-tile software and evaluated the associations between Tim-3 and overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…A recent study highlighted the potential significance of upregulated Tim-3 as a prognostic marker, indicating an unfavorable prognosis for individuals diagnosed with AML. Moreover, the biological properties of Tim-3 were found to be associated with immune responses and signaling pathways involved in the regulation of LSCs 13 . The identification of hub genes displaying differential expression levels in relation to Tim-3 may offer valuable opportunities to deepen our understanding of prognosis and the role of LSCs within the Tumor Immune Microenvironment (TME) of AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study highlighted the potential significance of upregulated Tim-3 as a prognostic marker, indicating an unfavorable prognosis for individuals diagnosed with AML. Moreover, the biological properties of Tim-3 were found to be associated with immune responses and signaling pathways involved in the regulation of LSCs 13 . The identification of hub genes displaying differential expression levels in relation to Tim-3 may offer valuable opportunities to deepen our understanding of prognosis and the role of LSCs within the Tumor Immune Microenvironment (TME) of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by analyzing somatic mutations, it has been determined that multistep leukemogenesis arises from self-renewing HSCs, highlighting Tim-3 as a potential target for selectively eliminating LSCs while preserving residual HSCs 11 . In a recent investigation involving 302 AML patients, Tim-3 was detected in LSCs at the time of initial diagnosis in 78.5% of cases 12 , 13 . Moreover, Tim-3 serves as an immune checkpoint and plays a critical role in immune responses during AML 14 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This interaction is known to negatively regulate CD8+ T-cell activation and Th1-type immunity by inducing cell death ( 107 ). TIM-3 appears to be a marker of exhaustion and an increased number of exhausted PD-1 + /TIM-3 + CD8 + T-cells has been associated with disease progression and poorer prognosis in AML ( 108 , 109 ). Preliminary in vivo studies have shown that blockade of TIM-3 prevents engraftment of leukemic stem cells without inhibiting normal stem cell engraftment ( 110 ).…”
Section: Other Targetable Checkpoint Moleculesmentioning
confidence: 99%
“…These cell surface markers have diverse cellular roles which co-ordinate the external stimuli to the internal cellular environment. Inhibitory immune checkpoint receptors, such as TIM-3 and PD-L1, have been associated with poor survival and are implicated in hypomethylating agent resistance [7][8][9]. Furthermore, epigenetic gene silencing of activating immune receptor genes in AML has been observed; the expression of which can be shown to be rescued upon treatment with HDACi [10].…”
Section: Defining the Lsc: Function Over Formmentioning
confidence: 99%